PENGARUH PENGAWASAN KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU PADA SEKOLAH MENENGAH KEJURUAN NEGERI 1 DAYUN KECAMATAN DAYUN KABUPATEN SIAK - Dewi, Diana Sri; Nikmah, Junita Ulfatun (Eko dan Bisnis: Riau Economic and Business Review, 2022)
The cornerstone of this study is that principals are also responsible for improving the quality of education, as set forth in the Basic Education Act No. 28 of 1990. This study aimed to determine whether the principal's oversight Does the principal influence teacher discipline at Dayun State Vocational High School 1 Dayun, Dayun County, Siak Regency. In this study, data was collected through questionnaires from 35 teachers. Quantitative analysis includes verification, reliability testing, and normality testing. Data analysis technique using a simple linear test, which is used to test hypothesis using t-test and deterministic test. From the results of data processing via SPSS, the number of t is 5,511, and from the percent distribution of t, the table t is 2,03 . While the table t count > t, and the significance level is also 0.000 andlt; 0.05. Therefore, the results of hypothesis testing in this study indicate that the principal's supervision has an influence on the work discipline of teachers at Bang 1 Dayun Vocational High School, Dayun District, Siak Regency. The relationship between the supervisor variable (X) and work discipline (Y) is positive, as evidenced by a regression coefficient of 0.532, which means that every 1% increase in the monitored variable will increase the work discipline variable. of teachers at Vocational School 1 Dayun School by 0,532. The value of the coefficient of determination (R squared) is 0. 79. Principal supervision had a 7.90% influence on teacher work discipline at State 1 Dayun Vocational High School, Dayun District, Siak Regency